Who feeds the World? - Girls - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Dr. Ir. Maarten Van Ginkel, Deputy Director Genral- Research, ICARDA (International Center for Agriculture Research in the Dry Areas) talks about the importance of Gender and Youth prospective in the research agenda. Video by Meerim Shakirova, social media reporter